Religion after Enlightenment: the case for Islam - Reçber, Mehmet Sait (Islam and Christian-Muslim relations, 2012)
This article analyses from an Islamic viewpoint the Enlightenment call to take up the intellectual and moral responsibility of using one's reason and understanding in religious matters. The first and second sections present a critical examination of the ideas of reason and justification advanced by Enlightenment philosophers such as Kant, and a counter-development of these ideas after the Enlightenment as exemplified in MacIntyre's thought. Having concluded that both of these approaches are untenable for a variety of reasons, the final section argues that a meta-epistemological perspective stipulated by Islam can both square with the original call of the Enlightenment and shed light on further discussion of various issues such as reason, religion and revelation.